International investment law : reconciling policy and principle - Subedi, Surya P. , 1958- (Hart Publishing, 2012)
This second edition offers an up-to-date, scholarly overview of the law of foreign investment, incorporating a thorough and succinct analysis of the principles and standards of treatment available to foreign investors in international law